Assassination of Alexander II in Cases of Insulting Majesty (Material from Tambov Province) - K. V. Samokhin (Научный диалог)
This article examines the judicial and investigative cases concerning insults to the Majesty, as reviewed by the Tambov Provincial Gendarmerie in 1881. A comprehensive quantitative analysis of the episodes contained within these cases is conducted, focusing on the assassination of Alexander II as a catalyst for such offenses. The study considers the social backgrounds of the defendants and the geographical context of the insults. A classification of the identified instances is provided based on the presence or absence of denunciation (informing) in the cases, as well as the causal relationships leading to the offenses. All episodes are divided into those that are perceived as fictitious and those without denunciation; the latter are further categorized into three groups: 1) those confirming the desacralization of the image of a specific monarch, 2) those indicating the onset of a dilution of monarchism through the desacralization of Alexander II’s image, and 3) those evidencing the desacralization of monarchy itself. The quantitative and qualitative analysis of these cases suggests that by 1881, a devaluation of the monarchical principle was already present in the worldview of Russian society. However, given the number of relevant judicial and investigative episodes, as well as instances unrecorded by local gendarmerie authorities, a definitive conclusion cannot be drawn. The author posits that the assassination of Alexander II should be viewed not only as an indicator of rising anti-monarchical sentiments but also as a trigger for the emergence of this trend.